Pre-injection of exosomes can significantly suppress ovarian cancer growth by activating the immune system in mice - Yuanyuan Wang; Changyi Zhang; Huimin Zeng; Liangliang Wang; Zanhong Wang; Zhiqiang Han (Cancer Immunology, Immunotherapy, 2025)
Abstract As a type of “cold tumor” with limited immune cell infiltration, ovarian cancer has historically shown limited efficacy in immunotherapy. In this study, we report that exosomes from ovarian cancer can specifically target omentum which is the predilection site for ovarian cancer to metastasize and combat subsequently implanted tumor. Furthermore, we found a substantial increase in the proportion of CD3 + T cells, particularly CD8 + T cells, within the omental tissue where exosomes homed. This increase was accompanied by a significant enhancement in granzyme B levels within CD8 + T cells. Additionally, there was a notable elevation in the concentration of interferon-gamma (IFN-γ) in peripheral blood. In vitro results indicated that exosomes could be internalized by dendritic cells (DCs), promote DC differentiation, and subsequently induce the production of granzyme B and IFN-γ in T cells. Surprisingly, we also observed high expression of programmed death ligand 1 (PD-L1) in the omentum. Therefore, we discovered whether combining PD-L1 blockade led to further tumor regression. However, although the combination group showed complete tumor regression, this difference did not reach statistical significance. But in general, we emphasize that in the case of pre-injection, exosomes have great potential to combat the famous “cold tumor”, ovarian cancer, via targeting omentum and activating anti-tumor immunity, offering a novel avenue for overcoming ovarian cancer.